Relasi Muslim dan Non Muslim Menurut Nahdlatul Ulama: Studi Atas Hasil-Hasil Keputusan Bahth Al Masail Nahdlatul Ulama - Luthfi Hadi Aminuddin (Justicia Islamica, 2014)
Aswaja ideology developed by NU has five characteristics; tawassut, tasmuh, tawazun, ta'adul and amr ma'ruf nahy an munkar. This paper wants to take a closer look at the results of the fatwa of NU clerics about Muslim relations with non-Muslims based on the five characteristics above. NU's fatwas on Muslim relations with non-Muslims can be classified into two typologies; fatwas on akidah and fatwas on mu'amalah, with different characteristics. fatwas of NU clerics related to issues categorized as ritual-akidah-theological character tend to be exclusive. While NU fatwas on mu'amalah are inclusive.